Volume and Type of Alcohol During Early Pregnancy and the Risk of Miscarriage. (19th September 2014) - Avalos, Lyndsay Ammon; Roberts, Sarah CM; Kaskutas, Lee Ann; Block, Gladys; Li, De-Kun
<x xml:space="preserve">Abstract</x> Background: Research on alcohol consumption during pregnancy and miscarriage spans over three decades, yet the relationship is still not well-understood. Objectives: To assess the relationship between volume and type of alcohol consumed during pregnancy in relation to miscarriage. Methods: We utilized data from a population-based cohort study of pregnant women (n = 1061) of which 172 (16%) women had a miscarriage. Upon study entry, participants were asked about their alcohol consumption during pregnancy. Based on the average number of drinks per week, women were categorized into one of three categories: four or more drinks per week (n = 32, 3%), less than four drinks per week (n = 403, 38%), and no alcohol intake (n = 626, 59%). In addition, women were categorized by the type of alcohol beverage they consumed: beer only (n = 47, 4%), spirits only (n = 56, 5%), wine only (n = 160, 15%), or a combination of two or more types of alcohol (n = 172, 16%). Results: A significant increased risk of miscarriage (adjusted hazard ratio (aHR): 2.65; 95% confidence interval (CI): 1.38, 5.10) was found for women who drank four or more drinks a week. Our findings also suggest the relationship between alcohol intake during pregnancy and miscarriage is strongest for miscarriage occurring prior to 10 weeks of gestation. In addition, women who drank only spirits had more than a two-fold increased risk of miscarriage compared to women who abstained (aHR: 2.24; 95% CI: 1.32, 3.81). Conclusions/Importance: Future research assessing the factors that may contribute to an increased risk of miscarriage should consider the type of alcohol consumed.